2020
DOI: 10.1017/s0021932020000413
|View full text |Cite
|
Sign up to set email alerts
|

Genetic load and biological changes to extant humans

Abstract: Extant humans are currently increasing their genetic load, which is informing present and future human microevolution. This has been a gradual process that has been rising over the last centuries as a consequence of improved sanitation, nutritional improvements, advancements in microbiology and medical interventions, which have relaxed natural selection. Moreover, a reduction in infant and child mortality and changing societal attitudes towards fertility have led to a decrease in total fertility rates (TFRs) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Indeed, Crow [2] made the argument originally in the context of environmental improvements in human societies and their effect on genetic variation. Consistent with his predictions, recent comparative genomic analyses have revealed a greater incidence of genetic pathologies in western industrialized populations than in traditional, pre-industrial human societies which are more exposed to natural selection [3,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 66%
“…Indeed, Crow [2] made the argument originally in the context of environmental improvements in human societies and their effect on genetic variation. Consistent with his predictions, recent comparative genomic analyses have revealed a greater incidence of genetic pathologies in western industrialized populations than in traditional, pre-industrial human societies which are more exposed to natural selection [3,[36][37][38][39].…”
Section: Discussionmentioning
confidence: 66%
“…However, other factors related to human evolution must be taken into account. For example, Saniotis et al (2021) point out that the directional factors of evolution are mutations and natural selection. According to the authors of this publication, it cannot be excluded that the observed variation in selected muscles is the result of a single mutation that disrupts or alters the process of fetal development.…”
Section: Discussionmentioning
confidence: 99%
“…Better quality housing, improved diets, and benevolent social activities, such as a welfare state or the universal provision of medical care, are suggested to have been particularly influential in preventing natural selection from purging deleterious mutations in human populations [1, 2, 4, 5]. Consistent with this suggestion, recent comparative genomic analyses have revealed a greater incidence of genetic pathologies in western industrialised populations than in traditional, pre-industrial human societies which are more exposed to natural selection [4, 5, 7-9]. Nevertheless, it is impossible to demonstrate that a more benign physical and social environment, in which selection is relaxed, has caused this difference.…”
Section: Introductionmentioning
confidence: 98%
“…Benevolent social activities, such as the widely available provision of medical care, are suggested to have been particularly influential in preventing natural selection from purging deleterious mutations [2][3][4] . Consistent with this suggestion, recent comparative genomic analyses have revealed a greater incidence of genetic pathologies in western industrialised populations than in more traditional human societies [3][4][5][6][7] -though it is impossible to demonstrate that benevolent social behaviours have caused this difference.…”
mentioning
confidence: 99%
See 1 more Smart Citation